Control of Design Documentation - Sadirov Shokhrukh Makhamasadikovich (Genius Publishing Group, 2022)
This article analyses the management of the correct sequence of work performed in the development of design documentation, the organization of work on the inspection of developed drawings, diagrams, etc.
Keywords: drawings; design documentation; control; quality